Anatomy Of The Human Body As an Expression Of Painting Creation - Putra, Kadek Win Mahesa; Ruta, I Made; Tjokropramono, I Gede Yosef (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
In this Independent Project MBKM TA report, the author raises the title “Anatomy Of The Human Body As an Expression Of Painting Creation” which originated from the author’s daily activities when looking in the mirror in front of glass cabinet of the room which finally sparked the author’s idea to create works of painting. The problem is how to visualize the anatomical form of the human body in each work. In realizingit, the author uses methods and techniques obtained during the MBKM process. The purpose and benefits are to develop the author’s creativity in expressing expressive and semi-realist forms in the process of creating works. As well as using a method of creation that includes several stages, namely, contemplation, exploration, improvisation, realization/formation. From this process  the author produced six works entitled : 1) “Walking”, 2) “Behind”, 3) “Grasping”, 4) “Leaning”, 5) “Hearing”, 6) “ Trail II”. It can be concluded that the author created the work based on his interest in the anatomical form of the human body, with ideas that come from the author’s daily experience through direct observation and digital media sources. In the realization stage, the author combines techniques from the results of MBKM and teaching obtained on campus, to be realized in the form of two dimensional works. From all processes, the author tries to get characteristics in painting.